2022
DOI: 10.1002/1878-0261.13303
|View full text |Cite
|
Sign up to set email alerts
|

The antiviral drug telaprevir induces cell death by reducing FOXA1 expression in estrogen receptor α (ERα)‐positive breast cancer cells

Abstract: Previously, we found that telaprevir (Tel), the inhibitor of hepatitis C virus NS3/4A serine protease, reduces estrogen receptor a (ERa) content at the transcriptional level without binding to the receptor, prevents ERa transcriptional activity, and inhibits basal and 17b-estradiol (E2)-dependent cell proliferation in different breast cancer (BC) cell lines. Here, we further characterize the Tel action mechanisms on ERa levels and function, identify a possible molecular target of Tel in BC cells, and evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 62 publications
0
8
0
1
Order By: Relevance
“…Recently, we demonstrated that the antiviral drug telaprevir (Tel) induces degradation of the ERα and hampers the proliferation of several ERα-positive BC cell lines 23,24 . Given the sensitivity of ERα-positive BC cell lines to various kinase inhibitors (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we demonstrated that the antiviral drug telaprevir (Tel) induces degradation of the ERα and hampers the proliferation of several ERα-positive BC cell lines 23,24 . Given the sensitivity of ERα-positive BC cell lines to various kinase inhibitors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also used a hypothesis-driven approach to identify additional kinases involved in regulating receptor intracellular levels by conducting Affymetrix analyses on ERα-positive BC cells treated with telaprevir (Tel), an antiviral drug inducing ERα degradation by inhibiting the kinases IGF1-R and AKT 23,24 . Surprisingly, we found that Tel reduced the mRNA levels of many kinases, most of which belonged to the kinase signature that distinguishes LumA BC from basal BC 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wykazano, że telaprevir zmniejsza wewnątrzkomórkowe poziomy ERα, dereguluje sygnalizację E2:ERα i hamuje proliferację indukowaną przez E2 w komórkach raka piersi [23]. Sugeruje to potencjalne wykorzystanie telapreviru w leczeniu pierwotnego i przerzutowego raka piersi [24], lecz warto jednak przeprowadzić więcej badań klinicznych, które mogłyby ocenić ewentualne działania niepożądane tego leku przed rozpoczęciem badań klinicznych z udziałem ludzi.…”
Section: Rak Piersiunclassified
“…Furthermore, we have previously reported a selection of Food and Drug Administration (FDA)-approved drugs that do not directly bind to the ERα but have the ability to induce its degradation by activating various cellular pathways [5][6][7][8]. These drugs have also demonstrated the capability to inhibit the proliferation of cells expressing the Y537S ERα variant [5][6][7][8]. This indicates that promoting the degradation of ERα is su cient to hinder cell proliferation, regardless of the drug's ability to directly bind to the receptor [3].…”
Section: Introductionmentioning
confidence: 99%